Trends of burning mouth syndrome: a bibliometric study - Lin, Xuanyu; Jin, Ruihui; Huang, Wanyu; Ye, Yicai; Jin, Jing; Zhu, Wenzong (Frontiers in Neurology, 2024)
Objectives: This study utilizes bibliometric analysis to map the current research landscape and forecast emerging trends within the domain of Burning Mouth Syndrome (BMS).: A comprehensive review of literature related to BMS was conducted, drawing from the Web of Science Core Collection (WoSCC) from 2008 to 2023. The analysis included both publication types "Article" and "Review Article". Advanced quantitative techniques and visual analytics tools, including CiteSpace, VOSviewer, Tableau, and the Map Equation online platform were utilized to analyze the academic publications within this domain.Results: Our analysis incorporated 497 articles on BMS. The data exhibit a progressive increase in the annual volume of publications from 2008 to 2023. In terms of geographic and institutional contributions, the United States of America (with 80 publications) and Nihon University (with 26 publications) emerged as leading entities in BMS research, while the Netherlands and England were identified as central to international collaboration efforts. Prominent researchers in this field include Adamo Daniela (18 publications) and Sun Andy (16 publications). Furthermore, the most cited works were authored by Jääskeläinen SK. An examination of the journals in which these articles were published showed a dominance of dental journals, highlighting significant interest and research efforts in BMS within the dental research community.The steady growth in BMS research signifies the formation of a robust core of researchers and demonstrates the maturation of the field. Despite this progress, the findings highlight a notable deficiency in cross-institutional and cross-regional collaborative efforts. Keyword cluster analysis has revealed "management" as a persistently relevant theme, with "pain modulation" emerging as the current focal interest.Additionally, "blood profile", "pernicious anemia", and "folate" have been identified as prospective areas of growing interest, suggesting important directions for future investigations.Clinical Relevance: This bibliometric analysis reveals the research landscape of BMS, aiming to highlight potential collaborative opportunities and define future research directions. These insights are invaluable for guiding subsequent investigations and carving new paths in the exploration of BMS.